Implementation of Labour Commitments in Vietnam’s New Generation Free Trade Agreements and Experience from International Disputes - Quan, Ngo Trong (VNU Journal of Science: Legal Studies; Vol 38 No 3DO - 10.25073/2588-1167/vnuls.4416, 2022)
Commitments on labor standards or trade and sustainable development recently emerge in new-generation free trade agreements (FTAs) of Vietnam including the CPTPP or EVFTA. Member states shall enforce their labor laws in a manner that does not interfere with free and fair trade and investment. This article analyzes the tribunals’ decisions in the only two disputes in the world to date arising from violations of labor commitments in FTAs, including disputes of the Dominican Republic - Central America - United States FTA (CAFTA-DR) and the EU-Korea FTA. On the basis of similar commitments of Vietnam, this article draws some lessons for better implementation of its FTAs’ labor commitments.